Legal and institutional tools to mitigate plastic pollution affecting marine species: Argentina as a case study - González Carman, Victoria (2015)
Plastics are the most common form of debris found along the Argentine coastline. The Río de la Plata estuarine area is a relevant case study to describe a situation where ample policy exists against a backdrop of plastics disposed by populated coastal areas, industries, and vessels; with resultant high impacts of plastic pollution on marine turtles and mammals. Policy and institutions are in place but the impact remains due to ineffective waste management, limited public education and awareness, and weaknesses in enforcement of regulations. This context is frequently repeated all over the world. We list possible interventions to increase the effectiveness of policy that require integrating efforts among governments, the private sector, non-governmental organizations and the inhabitants of coastal cities to reduce the amount of plastics reaching the Río de la Plata and protect threatened marine species. What has been identified for Argentina applies to the region and globally.